Taṭbīq As-Sayyid ‘Abdullah Al- Ḥaddād Al-Adab As-Ṣūfi fi Qaṣidatihi “Ilzam Bāba Rabbika”: Wifqa Nazariyyat Al-Adab An-Nabawi li Kuntowijoyo - Aldjufri, Saleh; Tatik Maryatut Tasnimah (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2025)
Sayid Abdullah Al-Haddad was one of the leading Muslim intellectuals of his time who was also famous as a Sufistic writer. Among his kasidah compositions that are often hummed by activists of sholawat assemblies in Indonesia is Ilzam Bab Rabbik. This kasidah contains a moral message not to be too upset in living destiny and focus on seeking the pleasure of Allah SWT. This article aims to reveal Abdullah Al-haddad's Sufism practices contained in the kasidah and its relevance to prophetic literature. The research data is in the form of kasidah Ilzam Bab Rabbik taken from the Diwan Al-Haddad poetry anthology using reading and recording techniques which include sorting and classifying data into tables. Then the data is analyzed using the hermeneutic method that has been classified according to the rules of prophetic literature, namely humanization, liberation, and transcendence. It is obtained from the results of this study that the kasidah Ilzam Bab Rabbik uses the mukhammas poem pattern (which emerged in the Abbasid era) and contains three prophetic literary concepts, namely humanization and liberation and transcendence with the dominance of the transcendence aspect. The formal and material objects of this kind of study are still not widely done, so this research is expected to contribute to realizing awareness and piety collectively in the Muslim community in particular.